INOVASI PELAYANAN BUNDAKU DALAM PENERBITAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TEMANGGUNG PROVINSI JAWA TENGAH - Aurora Tanjayani Munandar; Asep Hendra (Post Graduate School of Government Science, 2024)
The non-achievement of the birth certificate ownership target in the Dindukcapil Strategic Plan of Temanggung Regency led the Temanggung Regency Government to issue Regent Decree Number 470/363 of 2019 concerning the Acceleration Team for Increasing Civil Registration Certificate Ownership and the Team for Increasing Ownership of Population Registration Documents of Temanggung Regency. Following up on this, the latest service innovation called BUNDAKU began to be implemented by the Population and Civil Registration Office of Temanggung Regency. This study aims to know and understand the BUNDAKU Service Innovation in the issuance of birth certificates at the Population and Civil Registration Office of Temanggung Regency, to know and understand the obstacles of the BUNDAKU Service Innovation in the issuance of birth certificates, and to know the efforts made by the government related to the resolution of obstacles that BUNDAKU Service Innovation in the issuance of birth certificates at the Population and Civil Registration Office of Temanggung Regency. The research method used in this research is descriptive qualitative. The types of data used by researchers are primary data and secondary data. The data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the BUNDAKU Service Innovation in the issuance of birth certificates has not gone well because there are obstacles faced that hinder the service process such as the lack of required documents for the issuance of birth certificates